2000
DOI: 10.1074/jbc.m004639200
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Heat Shock Activation of ERK Mitogen-activated Protein Kinases in the Interleukin 3-dependent ProB Cell Line BaF3

Abstract: We have investigated heat shock stimulation of MAPK cascades in an interleukin 3-dependent cell line, BaF3. Following exposure to 42°C, the stress-activated JNK MAPKs were phosphorylated and activated, but p38 MAPKs remained unaffected. Surprisingly, heat shock also activated ERK MAPKs in a potent (>60-fold), delayed (>30 min), and sustained (>120 min) manner. These characteristics suggested a novel mechanism of ERK MAPK activation and became the focus of this study. A MEK-specific inhibitor, PD98059, inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…However, its role in apoptosis remains controversial, with several studies suggesting that it may play either a proapoptotic [44][45][46] or an antiapoptotic [47,48] role in this process. Available evidence also suggests that heat stress can activate MAPK1/3 [49,50]. In the later study [50], we demonstrated the activation of MAPK1/3 in monkey Sertoli cells after testicular hyperthermia.…”
Section: Discussionmentioning
confidence: 74%
“…However, its role in apoptosis remains controversial, with several studies suggesting that it may play either a proapoptotic [44][45][46] or an antiapoptotic [47,48] role in this process. Available evidence also suggests that heat stress can activate MAPK1/3 [49,50]. In the later study [50], we demonstrated the activation of MAPK1/3 in monkey Sertoli cells after testicular hyperthermia.…”
Section: Discussionmentioning
confidence: 74%
“…Preparation of Cellular Lysates-Cells (2 ϫ 10 7 ) were washed in cold phosphate-buffered saline and resuspended in lysis buffer (20 mM HEPES, pH 7.7, 2.5 mM MgCl 2 , 0.1 mM EDTA, 100 mM NaCl, 20 mM ␤-glycerophosphate, 20 g/ml leupeptin, 20 g/ml aprotinin, 100 g/ml phenylmethylsulfonyl fluoride, 100 M sodium orthovanadate, 500 M dithiothreitol, 1% (v/v) Nonidet P-40, 0.05% (v/v) Triton X-100) (26). Insoluble material was removed by centrifugation (20,800 ϫ g, 10 min, 4°C), the supernatants retained as the cellular lysates, and protein concentrations assayed (27).…”
Section: Gcsf-r Mutagenesis and Generation Of Stable Baf3mentioning
confidence: 99%
“…For assessment of JNK and ERK activity in the presence of the JNK inhibitor, Tat-TIJIP, lysate (200 g) from G-CSF-stimulated WT GCSF-R BaF3 cells was incubated with 40 g of GST-c-Jun or GST-Elk (26), complexes captured on glutathione-Sepharose 4B and divided into two aliquots. Samples were then treated with buffer or Tat-TIJIP (2 M) for 10 min at 30°C, prior to assaying of kinase activity by incubation with [␥-32 P]ATP as described above.…”
Section: Gcsf-r Mutagenesis and Generation Of Stable Baf3mentioning
confidence: 99%
“…Moreover, the induction of AP-1 activity by asbestos was thought to be mediated through the activation of MAPK family, ERK1 and ERK2. The activation of ERK by proinflammatory stimuli was also thought to play important roles in innate immune responses and autoimmunity (Ng and Bogoyevitch 2000;Shaul and Seger 2007).…”
Section: Discussionmentioning
confidence: 99%